Study on the Coordination of Cd Ion with Perhydroxylated Hetero-N and Hetero-S Calixtetraarene Derivatives. Issue 1 (1st December 2022) - Liu, Yu; Wang, Xiaofeng; He, Liping; Meng, Yanbin; Lan, Wenbo; Wang, Binbin; Yu, Yao; Xie, Qun
Abstract: To explore the best hybrid calixarene for cadmium ion capture, the B3LYP method in density functional theory (DFT) was used to optimize the structure and infrared vibration data of the complexes formed by each fully hydroxylated heteroN and heteroS calixtetraarenes with Cd ions. The stability of the structure of each complex was verified. At the same time, the structural characteristics of each complex were analyzed. A comparative study on the binding ability of different numbers of hybrid calix [4] arene derivatives to Cd ions was carried out, and the complexes that best bound to Cd ions were obtained. For example, the binding capacity of hetero S-calix [4] arenes to Cd ions is greater than that of non-hybrid complexes and hetero-N complexes to Cd ions. More interestingly, as the number of S atoms in the hetero S increases, the binding ability to Cd becomes stronger.